Weather-resistant puncture-resistant environment-friendly dirt collection bag material and preparation method thereof

By coating the surface of talc with silica, the puncture resistance and weather resistance of the environmentally friendly sewage collection bag material are improved, solving the problems of puncture by sharp objects and material damage under high temperature environments, and achieving a longer service life and a more stable structure.

CN120840200APending Publication Date: 2025-10-28浙江明士达股份有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510887221.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-30
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

Existing environmentally friendly waste collection bags are easily damaged when punctured by sharp objects or exposed to high temperatures, resulting in a shortened service life and unstable material properties.

Method used

A method of coating talc powder with silica is adopted. A silica coating layer is formed on the surface of talc powder by using a silane coupling agent, which improves the compatibility and interfacial bonding between talc powder and polymer matrix, forming a composite reinforcement system and enhancing the puncture resistance and structural stability of the material.

Benefits of technology

It significantly improves the material's puncture resistance and structural stability, extends its service life, and improves its material properties in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a weather-resistant puncture-resistant environment-friendly dirt collection bag material and a preparation method thereof, and relates to the technical field of environment-friendly dirt collection bags. The preparation method comprises the following steps: stirring and mixing PVC resin powder, a plasticizer, a low-temperature-resistant plasticizer, talcum powder surface-coated silicon dioxide, titanium dioxide and other materials, banburying, milling, filtering, calendering, cooling, trimming and curling to obtain a PVC film layer; the preparation method comprises the following steps: taking EPVC (Ethylene Polyvinyl Chloride) paste resin, a plasticizer and an adhesive as a base cloth layer, stirring the EPVC paste resin, the plasticizer and the adhesive into uniform thick slurry, uniformly coating the base cloth with the thick slurry, and drying to form a PVC coating; the base cloth with the PVC coating and the PVC film are heated and attached to form the composite coated cloth, and the composite coated cloth is obtained after cooling, edge cutting and rolling. The invention aims to provide the weather-resistant puncture-resistant environment-friendly dirt collection bag material, so that the puncture resistance of a dirt collection bag is improved, the material performance of the dirt collection bag in a high-temperature environment is improved, and the structural stability of the dirt collection bag is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of environmentally friendly waste collection bags, specifically to a weather-resistant and puncture-resistant environmentally friendly waste collection bag material and its preparation method. Background Technology

[0002] Among numerous environmental protection measures and tools, environmentally friendly waste collection bags, as a key piece of equipment specifically designed for collecting and treating various pollutants, play an indispensable role in multiple fields such as industrial production, urban management, and daily life. In industrial production, they are widely used for collecting wastewater and waste residue. Wastewater and waste residue generated during industrial production often contain large amounts of harmful substances, which, if not properly treated, can cause serious environmental pollution. Waste collection bags effectively collect these pollutants, preventing their spread into the surrounding environment and facilitating subsequent treatment and disposal. In urban management, urban sewer cleaning is a crucial link in ensuring the normal operation of the city and the quality of life for residents. The debris removed often contains various sharp branches, wires, etc., which waste collection bags can safely contain, preventing secondary pollution to the environment. In daily life, waste collection bags are also widely used in the treatment of sewage and garbage, playing an important role in maintaining a good living environment.

[0003] In practical applications, sludge collection bags frequently come into contact with various sharp objects, which is one of the main causes of their damage. During the collection of industrial waste and wastewater, the waste may contain sharp impurities such as metal scraps and broken stones. These sharp objects can easily puncture and damage the bags during handling and transportation, leading to pollutant leakage. Similarly, in urban sewer cleaning, the debris removed may contain sharp branches, wires, etc., which also pose a threat to the sludge collection bags. Even during ordinary household waste collection, small sharp objects such as discarded can pull tabs and toothpicks can inadvertently puncture the bags, causing garbage to scatter and seriously affecting environmental sanitation. Furthermore, climate significantly impacts the lifespan of environmentally friendly sludge collection bags. At high temperatures, the material of the bags easily softens and deforms, leading to a decrease in structural stability. Therefore, this invention provides a weather-resistant, puncture-resistant environmentally friendly sludge collection bag material and its preparation method. Summary of the Invention

[0004] The purpose of this invention is to provide a weather-resistant, puncture-resistant, environmentally friendly waste collection bag material and its preparation method, which improves the waste collection bag's resistance to puncture by sharp objects, enhances the material properties of the waste collection bag in high-temperature environments, strengthens its structural stability, and extends its service life.

[0005] On one hand, the present invention provides a weather-resistant, puncture-resistant, and environmentally friendly waste collection bag material, the steps of which include:

[0006] (1) PVC resin powder, plasticizer, low temperature resistant plasticizer, talc powder are coated with silica, titanium dioxide, stabilizer, antioxidant, ultraviolet absorber, mildew and antibacterial agent, and calcium powder. After stirring and mixing, the mixture is then subjected to intensive mixing, open milling, filtration, calendering, cooling, edge trimming and rolling to obtain PVC film layer.

[0007] (2) Polyester woven fabric is used as the base fabric layer. EPVC paste resin, plasticizer and adhesive are stirred into a uniform thick slurry, which is then uniformly coated on the base fabric and dried to form a PVC coating.

[0008] (3) The base fabric with PVC coating is heated and bonded to the PVC film to form a composite coated fabric, which is then cooled, trimmed, and rolled up to obtain the final product.

[0009] Further, the PVC film layer comprises the following raw materials in parts by weight: 85-95 parts PVC resin powder, 40-50 parts plasticizer, 4-5 parts low-temperature resistant plasticizer, 10-12 parts talc powder coated with silica, 3-4 parts titanium dioxide, 2-3 parts stabilizer, 0.15-0.2 parts antioxidant, 0.15-0.2 parts ultraviolet absorber, 0.2-0.4 parts mildew and antibacterial agent, and 4-5 parts calcium powder.

[0010] Furthermore, the preparation method of the talc powder coated with silica includes: adding silane coupling agent KH-570 to a mixture of ethanol and water, hydrolyzing to obtain a silane coupling agent hydrolysate; drying talc powder and adding it to the hydrolysate, stirring, filtering, washing and drying to obtain modified talc powder; ultrasonically dispersing the modified talc powder in ethanol and stirring to obtain mixture A; mixing tetraethyl orthosilicate with ethanol and stirring to obtain mixture B; adding mixture A to mixture B for reaction, aging, centrifugation to obtain a gel, and then drying and calcining to obtain the final product.

[0011] Further, the hydrolysis conditions of the silane coupling agent hydrolysate are as follows: hydrolysis at 25±2℃ and 550-650rpm for 25-35min, with acetic acid adjusting the pH to 5.0±0.1; the stirring conditions of the modified talc powder are as follows: constant temperature stirring at 55-65℃ and 250-350rpm for 2-3h; the stirring conditions of mixture A are as follows: constant temperature stirring at 40±1℃ and 450-550rpm; the stirring conditions of mixture B are as follows: pH adjusted to 9.5±0.1 with ammonia water, stirring at 40±1℃ and 450-550rpm for 10-20min; the reaction time of mixture A added to mixture B is 3-4h, and the aging time is 20-24h.

[0012] Further, the calcination is performed by heating from 25°C to 250-350°C at a heating rate of 2°C / min, holding at that temperature for 50-60 min, and then heating to 450-550°C at a heating rate of 5°C / min, holding at that temperature for 120-140 min to obtain the final product.

[0013] Furthermore, the linear density of the base fabric is 1000D×1000D, and the width is 28×26 threads / inch.

[0014] Furthermore, the low-temperature resistant plasticizer is dioctyl adipate; the stabilizer is barium zinc stabilizer; the ultraviolet absorber is 2-hydroxy-4-n-octyloxybenzophenone; the antifungal and antibacterial agent is N-(trichloromethylthio)phthalimide; and the antioxidant is antioxidant 1010.

[0015] Furthermore, the weight ratio of EPVC paste resin, plasticizer, and adhesive in the PVC coating is 65-75:50-60:10-14.

[0016] Furthermore, the plasticizer is a DOTP plasticizer; the adhesive is a polyurethane adhesive.

[0017] On the other hand, the present invention also provides a weather-resistant, puncture-resistant, environmentally friendly waste collection bag material, which is prepared using the aforementioned method.

[0018] The beneficial effects of this invention are as follows:

[0019] This invention uses silica-coated talc as a filler. Talc itself has a certain lamellar structure, which can increase the toughness of the material to a certain extent. However, talc has poor compatibility with the polymer matrix and is prone to agglomeration, which leads to weak interfacial bonding, stress concentration, and thus reduced material performance. Silica, on the other hand, has a high specific surface area and good chemical stability. By coating talc with silica, the compatibility between talc and the polymer matrix can be improved, allowing talc to be better dispersed in the matrix, reducing agglomeration, and enhancing interfacial bonding. Furthermore, the rigid particles of silica can complement the lamellar structure of talc to form a composite reinforcement system, leveraging both the toughening effect of talc and the reinforcing effect of silica, thereby significantly improving the material's puncture resistance and tensile strength.

[0020] Compared to other fillers, such as titanium dioxide, pure silica, or untreated / modified talc alone, none can achieve this synergistic effect of reinforcement and toughening. Titanium dioxide has poor compatibility with the matrix and poor dispersion of rigid particles, which weakens the material's puncture resistance and low-temperature resistance; pure silica has a high specific surface area and is prone to agglomeration, and lacks the toughening effect of lamellar talc, leading to increased brittleness; untreated / modified talc has poor compatibility with polymers, weak interfacial bonding, and is prone to agglomeration, causing stress concentration. Therefore, talc coated with silica plays an irreplaceable role in the material.

[0021] The preparation process of coating talc powder with silica in this invention also embodies the synergistic principle. In the preparation process, silane coupling agent KH-570 is first hydrolyzed in a mixture of ethanol and water to obtain a silane coupling agent hydrolysate. Then, dried talc powder is added to the hydrolysate for stirring and modification. One end of the silane coupling agent can chemically react with the hydroxyl groups on the surface of talc powder to form a chemical bond, while the other end can react with the silica precursor, thereby forming a uniform silica coating layer on the surface of the talc powder. This preparation method utilizes the bridging effect of the silane coupling agent to achieve effective bonding between talc powder and silica. The silane coupling agent not only improves the interfacial compatibility between talc powder and silica but also enhances the bonding force between them. Detailed Implementation

[0022] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0023] It should be noted that the PVC resin powder used in this invention was purchased from Hebei Jinniu Chemical Co., Ltd.; the EPVC paste resin was purchased from Shanghai Kaiyin Chemical Co., Ltd.; and other raw materials not specified are commercially available.

[0024] Example 1

[0025] This embodiment provides a weather-resistant, puncture-resistant, and environmentally friendly waste collection bag material, the steps of which include:

[0026] (1) 90 parts of PVC resin powder, 45 parts of plasticizer, 4.5 parts of low temperature resistant plasticizer, 11 parts of talc powder coated with silica, 3.5 parts of titanium dioxide, 2.5 parts of stabilizer, 0.17 parts of antioxidant, 0.18 parts of ultraviolet absorber, 0.3 parts of mildew and antibacterial agent, and 4.5 parts of calcium powder were mixed by stirring and then subjected to intensive kneading, open kneading, filtering, calendering, cooling, edge trimming and rolling to obtain a PVC film layer with a thickness of 0.15 mm;

[0027] The preparation method of talc powder coated with silica includes: adding 1.5g KH-570 to a mixture of 150mL ethanol and 15mL water, hydrolyzing at 25℃ and 600rpm for 30min, and adjusting the pH to 5.0 with 1M acetic acid to obtain a silane coupling agent hydrolysate; drying talc powder at 105℃ for 2.5h, then adding 80g to the hydrolysate, stirring at 60℃ and 300rpm for 2.5h, filtering, washing three times with ethanol, and vacuum drying at 80℃ for 4h to obtain modified talc powder; dispersing the modified talc powder in 300mL ethanol by ultrasonication at 300W for 30min, and stirring at 500rpm and 40℃ to obtain mixture A; and mixing 20g tetraethyl orthosilicate with 300mL ethanol... The alcohols were mixed, and the pH was adjusted to 9.5 with ammonia. After stirring at 40℃ and 500rpm for 15min, a mixture B was obtained. Mixture A was added to mixture B and reacted for 3.5h, sealed and aged for 22h, centrifuged at 8000rpm for 10min, washed three times with ethanol to obtain a gel, and then vacuum dried at 80℃ for 12h. The temperature was increased from 25℃ to 300℃ at a rate of 2℃ / min and held for 55min. The temperature was then increased to 500℃ at a rate of 5℃ / min and held for 130min to obtain the final product.

[0028] (2) Use a polyester woven fabric with a linear density of 1000D×1000D and a width of 28×26 threads / inch as the base fabric layer. Mix 70 parts of EPVC paste resin, 55 parts of plasticizer and 12 parts of adhesive into a uniform thick slurry, coat it evenly on the base fabric with a thickness of 0.2mm, and dry it to form a PVC coating.

[0029] The plasticizer is DOTP plasticizer; the low-temperature resistant plasticizer is dioctyl adipate; the stabilizer is barium zinc stabilizer; the ultraviolet absorber is 2-hydroxy-4-n-octyloxybenzophenone; the antifungal and antibacterial agent is N-(trichloromethylthio)phthalimide; the antioxidant is antioxidant 1010; and the adhesive is Henkel LOCTITE LIOFOL LA 2704.

[0030] (3) The base fabric with PVC coating and the PVC film are hot-pressed at 130°C and 10MPa for 3 minutes to form a composite coated fabric. After cooling, trimming and winding, the product is obtained.

[0031] Example 2

[0032] This embodiment provides a weather-resistant, puncture-resistant, and environmentally friendly waste collection bag material, the steps of which include:

[0033] (1) 85 parts of PVC resin powder, 40 parts of plasticizer, 4 parts of low temperature resistant plasticizer, 10 parts of talc powder coated with silica, 3 parts of titanium dioxide, 2 parts of stabilizer, 0.15 parts of antioxidant, 0.15 parts of ultraviolet absorber, 0.2 parts of mildew and antibacterial agent, and 4 parts of calcium powder are mixed by stirring and then subjected to intensive kneading, open kneading, filtering, calendering, cooling, edge cutting and rolling to obtain a PVC film layer with a thickness of 0.15 mm;

[0034] The preparation method of talc powder coated with silica includes: adding 1g KH-570 to a mixture of 140mL ethanol and 10mL water, hydrolyzing at 25℃ and 550rpm for 25min, adjusting the pH to 5.0 with 1M acetic acid to obtain a silane coupling agent hydrolysate; drying talc powder at 100℃ for 2h, then adding 80g to the hydrolysate, stirring at 55℃ and 250rpm for 2h, filtering, washing three times with ethanol, and vacuum drying at 80℃ for 4h to obtain modified talc powder; dispersing the modified talc powder in 300mL ethanol by ultrasonication at 300W for 30min, and stirring at 450rpm and 40℃ to obtain mixture A; and mixing 15g tetraethyl orthosilicate with 250mL ethanol. Mix the ingredients, adjust the pH to 9.5 with ammonia, and stir at 40℃ and 450rpm for 10min to obtain mixture B. Add mixture A to mixture B and react for 3h, seal and age for 20h, centrifuge at 8000rpm for 10min, wash three times with ethanol to obtain gel, then vacuum dry at 80℃ for 12h, heat from 25℃ to 250℃ at a heating rate of 2℃ / min, hold for 50min, heat to 450℃ at a heating rate of 5℃ / min, and hold for 120min to obtain the final product.

[0035] (2) Use a polyester woven fabric with a linear density of 1000D×1000D and a width of 28×26 threads / inch as the base fabric layer. Mix 65 parts of EPVC paste resin, 50 parts of plasticizer and 10 parts of adhesive into a uniform thick slurry, coat it evenly on the base fabric with a thickness of 0.2mm, and dry it to form a PVC coating.

[0036] The plasticizer is DOTP plasticizer; the low-temperature resistant plasticizer is dioctyl adipate; the stabilizer is barium zinc stabilizer; the ultraviolet absorber is 2-hydroxy-4-n-octyloxybenzophenone; the antifungal and antibacterial agent is N-(trichloromethylthio)phthalimide; the antioxidant is antioxidant 1010; and the adhesive is Henkel LOCTITE LIOFOL LA 2704.

[0037] (3) The base fabric with PVC coating and the PVC film are hot-pressed at 130°C and 10MPa for 3 minutes to form a composite coated fabric. After cooling, trimming and winding, the product is obtained.

[0038] Example 3

[0039] This embodiment provides a weather-resistant, puncture-resistant, and environmentally friendly waste collection bag material, the steps of which include:

[0040] (1) 95 parts of PVC resin powder, 50 parts of plasticizer, 5 parts of low temperature resistant plasticizer, 12 parts of talc powder coated with silica, 4 parts of titanium dioxide, 3 parts of stabilizer, 0.2 parts of antioxidant, 0.2 parts of ultraviolet absorber, 0.4 parts of mildew and antibacterial agent, and 5 parts of calcium powder are mixed by stirring and then subjected to intensive kneading, open kneading, filtering, calendering, cooling, edge cutting and rolling to obtain a PVC film layer with a thickness of 0.15 mm;

[0041] The preparation method of talc powder coated with silica includes: adding 2g of KH-570 to a mixture of 160mL ethanol and 20mL water, hydrolyzing at 25℃ and 650rpm for 35min, and adjusting the pH to 5.0 with 1M acetic acid to obtain a silane coupling agent hydrolysate; drying talc powder at 110℃ for 3h, then adding 80g to the hydrolysate, stirring at 65℃ and 350rpm for 3h, filtering, washing three times with ethanol, and vacuum drying at 80℃ for 4h to obtain modified talc powder; dispersing the modified talc powder in 300mL ethanol by ultrasonication at 300W for 30min, and stirring at 550rpm and 40℃ to obtain mixture A; and mixing 25g of tetraethyl orthosilicate with 350mL ethanol. Mix the ingredients, adjust the pH to 9.5 with ammonia, and stir at 40℃ and 550rpm for 20min to obtain mixture B. Add mixture A to mixture B and react for 4h, seal and age for 24h, centrifuge at 8000rpm for 10min, wash three times with ethanol to obtain gel, then vacuum dry at 80℃ for 12h, heat from 25℃ to 350℃ at a rate of 2℃ / min and hold for 60min, then heat to 550℃ at a rate of 5℃ / min and hold for 140min to obtain the final product.

[0042] (2) Use a polyester woven fabric with a linear density of 1000D×1000D and a width of 28×26 threads / inch as the base fabric layer. Mix 75 parts of EPVC paste resin, 60 parts of plasticizer and 14 parts of adhesive into a uniform thick slurry, coat it evenly on the base fabric with a thickness of 0.2mm, and dry it to form a PVC coating.

[0043] The plasticizer is DOTP plasticizer; the low-temperature resistant plasticizer is dioctyl adipate; the stabilizer is barium zinc stabilizer; the ultraviolet absorber is 2-hydroxy-4-n-octyloxybenzophenone; the antifungal and antibacterial agent is N-(trichloromethylthio)phthalimide; the antioxidant is antioxidant 1010; and the adhesive is Henkel LOCTITE LIOFOL LA 2704.

[0044] (3) The base fabric with PVC coating and the PVC film are hot-pressed at 130°C and 10MPa for 3 minutes to form a composite coated fabric. After cooling, trimming and winding, the product is obtained.

[0045] Comparative Example 1

[0046] In Comparative Example 1, the talc powder coated with silica was replaced with titanium dioxide coated with silica. The preparation steps were the same, except that the talc powder raw material was replaced with titanium dioxide. The rest was the same as in Example 1.

[0047] Comparative Example 2

[0048] In Comparative Example 2, the silica coating on the surface of talc powder was replaced with modified talc powder. The preparation steps included: adding 1.5g of KH-570 to a mixture of 150mL of ethanol and 15mL of water, hydrolyzing at 25℃ and 600rpm for 30min, adjusting the pH to 5.0 with 1M acetic acid to obtain a silane coupling agent hydrolysate; drying the talc powder at 105℃ for 2.5h, then adding 80g to the hydrolysate, stirring at 60℃ and 300rpm for 2.5h, filtering, washing three times with ethanol, and vacuum drying at 80℃ for 4h to obtain modified talc powder. The rest was the same as in Example 1, and the preparation steps were the same as in Example 1.

[0049] Comparative Example 3

[0050] In Comparative Example 3, the silica coating on the surface of the talc powder was replaced with talc powder, and the rest was the same as in Example 1, with the same preparation steps.

[0051] Comparative Example 4

[0052] In Comparative Example 4, the talc powder surface coating with silica was replaced with silica, and the rest was the same as in Example 1, with the same preparation steps.

[0053] Comparative Example 5

[0054] Comparative Example 5 did not include talc powder coated with silica as a raw material; otherwise, it was the same as Example 1, and the preparation steps were the same as in Example 1.

[0055] Comparative Example 6

[0056] Comparative Example 6 did not include titanium dioxide as a raw material, but the rest was the same as in Example 1, and the preparation steps were the same as in Example 1.

[0057] Experimental Example 1: The environmentally friendly waste collection bags prepared in Examples 1-3 and Comparative Examples 1-6 were tested as follows:

[0058] Puncture resistance: The test was conducted in accordance with GB / T 10004-2008 Plastic composite film and bag for packaging, dry lamination and extrusion lamination. A 100mm diameter sample was fixed with a ring clamp and punctured vertically with a 1mm diameter steel needle at a speed of 500mm / min. The maximum force (N) and puncture strength (MPa) were recorded.

[0059] Tensile strength: The test was conducted in accordance with GB / T 1040.3-2006 "Determination of tensile properties of plastics". A dumbbell-shaped specimen (25 mm long × 6 mm wide) was cut from the composite coated fabric for the test.

[0060] Weather resistance test: The test was conducted in accordance with GB / T 16422.2-2014 "Laboratory Light Source Exposure Test Methods for Plastics - Part 2: Xenon Arc Lamp". Xenon lamp aging (wavelength 340nm, irradiance 0.5W / m², 60℃ / 50%RH, 500h) was performed. The tensile strength before and after aging was tested and the retention rate was calculated.

[0061] Low-temperature toughness test: The test was conducted in accordance with GB / T 5470-2008 "Determination of Low-Temperature Embrittlement Temperature of Plastics". The specimen was impacted at -40℃, surface cracks were observed, and the embrittlement temperature was determined.

[0062] Five samples were tested in each group, and the average value was taken. The results are shown in Table 1 below:

[0063] Table 1

[0064] Based on the aforementioned data, it can be seen that Comparative Example 1 exhibits decreased puncture strength, decreased tensile strength, and inferior weather resistance and low-temperature toughness compared to the Example. The poor compatibility of titanium dioxide with the matrix leads to weakened interfacial bonding, and its rigid particle dispersion is also poor, further reducing the material's puncture resistance and low-temperature resistance.

[0065] Comparative Example 2 showed severe deterioration in weather resistance and insufficient mechanical properties; although the modification with silane coupling agent improved the initial dispersibility, the coupling agent hydrolyzed or broke down during long-term aging, leading to interface failure.

[0066] Comparative Example 3 showed a comprehensive decline in performance. The uncoated talc powder had poor compatibility with the polymer, weak interfacial bonding, and was prone to agglomeration, leading to stress concentration.

[0067] Comparative Example 4 showed insufficient mechanical strength, decreased low-temperature resistance, and the high specific surface area of ​​silica made it prone to agglomeration. Furthermore, the rigid particles lacked the toughening effect of lamellar talc, leading to increased brittleness.

[0068] Comparative Example 5 showed decreased puncture strength and tensile strength, poor weather resistance retention, and obvious cracks at -35℃. The lack of filler reinforcement resulted in weak matrix resistance to deformation, and the molecular chains were more susceptible to photo-oxidative aging damage.

[0069] Comparative Example 6 shows that the weather resistance and low-temperature toughness of titanium dioxide are impaired due to its omission. Titanium dioxide may delay photoaging through its ultraviolet shielding effect, but its absence makes the polymer chains more susceptible to degradation.

[0070] Finally, it should be noted that the above embodiments and comparative examples are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention; those skilled in the art should understand that modifications or equivalent substitutions can still be made to the present invention; and all technical solutions and improvements that do not depart from the spirit and scope of the present invention should be covered within the scope of the claims of the present invention.

Claims

1. A method for preparing a weather-resistant, puncture-resistant, environmentally friendly waste collection bag material, characterized in that the steps include... include: (1) PVC resin powder, plasticizer, low temperature resistant plasticizer, talc powder are coated with silica, titanium dioxide, stabilizer, antioxidant, ultraviolet absorber, mildew and antibacterial agent, and calcium powder. After stirring and mixing, the mixture is then subjected to intensive mixing, open milling, filtration, calendering, cooling, edge trimming and rolling to obtain PVC film layer. (2) Polyester woven fabric is used as the base fabric layer. EPVC paste resin, plasticizer and adhesive are stirred into a uniform thick slurry, which is then uniformly coated on the base fabric and dried to form a PVC coating. (3) The base fabric with PVC coating is heated and bonded to the PVC film to form a composite coated fabric. After cooling, trimming, and rolling, the product is obtained.

2. The weather-resistant, puncture-resistant, environmentally friendly waste collection bag material according to claim 1, characterized in that, The PVC film layer comprises the following raw materials in parts by weight: 85-95 parts PVC resin powder, 40-50 parts plasticizer, 4-5 parts low-temperature resistant plasticizer, 10-12 parts talc powder coated with silica, 3-4 parts titanium dioxide, 2-3 parts stabilizer, 0.15-0.2 parts antioxidant, 0.15-0.2 parts ultraviolet absorber, 0.2-0.4 parts mildew and antibacterial agent, and 4-5 parts calcium powder.

3. The weather-resistant, puncture-resistant, environmentally friendly waste collection bag material according to claim 2, characterized in that, The method for preparing talc powder coated with silica includes: adding silane coupling agent KH-570 to a mixture of ethanol and water, hydrolyzing to obtain a silane coupling agent hydrolysate; drying talc powder and adding it to the hydrolysate, stirring, filtering, washing and drying to obtain modified talc powder; ultrasonically dispersing the modified talc powder in ethanol and stirring to obtain mixture A; mixing tetraethyl orthosilicate with ethanol and stirring to obtain mixture B; adding mixture A to mixture B for reaction, aging, centrifugation to obtain a gel, and then drying and calcining to obtain the final product.

4. The weather-resistant, puncture-resistant, environmentally friendly waste collection bag material according to claim 3, characterized in that, The hydrolysis conditions for the silane coupling agent hydrolysate are as follows: hydrolysis at 25±2℃ and 550-650rpm for 25-35min, with the pH adjusted to 5.0±0.1 by acetic acid; the stirring conditions for the modified talc powder are as follows: constant temperature stirring at 55-65℃ and 250-350rpm for 2-3h; the stirring conditions for mixture A are as follows: constant temperature stirring at 40±1℃ and 450-550rpm; the stirring conditions for mixture B are as follows: pH adjusted to 9.0~10.0 by ammonia water, stirring at 40±1℃ and 450-550rpm for 10-20min; the reaction time for adding mixture A to mixture B is 3-4h, and the aging time is 20-24h.

5. The weather-resistant, puncture-resistant, environmentally friendly waste collection bag material according to claim 3, characterized in that, The calcination is performed by heating from 25°C to 250-350°C at a heating rate of 2°C / min, holding at that temperature for 50-60 minutes, then heating to 450-550°C at a heating rate of 5°C / min, and holding at that temperature for 120-140 minutes.

6. The weather-resistant, puncture-resistant, environmentally friendly waste collection bag material according to claim 1, characterized in that, The linear density of the base fabric is 1000D×1000D, and the width is 28×26 threads / inch.

7. The weather-resistant, puncture-resistant, environmentally friendly waste collection bag material according to claim 1, characterized in that, The low-temperature resistant plasticizer is dioctyl adipate; the stabilizer is barium zinc stabilizer; the ultraviolet absorber is 2-hydroxy-4-n-octyloxybenzophenone; the antifungal and antibacterial agent is N-(trichloromethylthio)phthalimide; and the antioxidant is antioxidant 1010.

8. The weather-resistant, puncture-resistant, environmentally friendly waste collection bag material according to claim 1, characterized in that, The weight ratio of EPVC paste resin, plasticizer, and adhesive in the PVC coating is 65-75:50-60:10-14.

9. The weather-resistant, puncture-resistant, environmentally friendly waste collection bag material according to claim 1, characterized in that, The plasticizer is a DOTP plasticizer; the adhesive is a polyurethane adhesive.

10. A weather-resistant, puncture-resistant, environmentally friendly waste collection bag material, characterized in that, The weather-resistant, puncture-resistant, environmentally friendly waste collection bag material is prepared using any one of claims 1-9.